The Influence of Corporate Culture on Business Performance. - Kučerová, Hana (My University, 2020)
Corporate culture is currently a very popular topic due to the rapid process of globalization and internationalization. The relationship between corporate culture and business performance has been researched in practice by many foreign scientists, however, in the Czech Republic, the connection between corporate culture and company performance in the past has been analyzed more on a theoretical level. This article aims to analyze the characteristics of a performance-enhancing corporate culture with a focus on creativity, motivation, and communication in a selected company. Furthermore, the comparison of results with theoretical background and suggestions for improvement. Analysis of corporate culture in the company Intrum Czech, Inc. was carried out using quantitative research.
Vliv podnikové kultury na podnikovou výkonnost.
Keywords: corporate culture; performance; evaluation; business; podniková kultura; výkonnost; hodnocení; podnikání